Interdisciplinary studies of the political order new applications of public choice theory - Boudreaux, Donald J.; Coyne, Christopher J.; Herzberg, Roberta Q. (Economy, polity, and society, 2019)
"The chapters in this volume explore and engage the key thinkers and ideas of the Virginia and Bloomington schools of political economy"--